EVALUASI EFISIENSI THERMAL POWER BOILER DENGAN MENGGUNAKAN METODE LANGSUNG - Imaniah Sriwijayasih; Eky Novianarenti; Dika Rahayu Widiana; Septaviola Dini Utami; Masaril Fatahilah; Adham Zaidaan Zulfaqar; Arya Zein Ariffadly, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
A boileris a device that produces steam or hot water by heating water or other fluids using heat energy from fuel. At PT.XYZ, there are two types of boilers, namely Power Boiler and Recovery Boiler Plant. Power Boiler produces steam with a pressure of 6300 kPa and a rate of 98 kg/s, while Recovery Boiler Plant produces steam from the digester extraction flow which is processed through flash tanks 1 and 2. Power Boiler uses BFB (Bubbling Fluidized Bed) technology with sand as a heating medium to burn rejects. This study analyzes the efficiency of waste-fired boilers at PT.XYZ Tanjung Enim using the direct method. The results of the analysis show that waste-fired boilers have a boiler efficiency value achieved of 60%, while the lowest boiler efficiency value is 33.4%. Factors that reduce boiler efficiency at PT.XYZ Tanjung Enim include waste which is the main fuel that still contains water content, cleanliness of the boiler tube surface, and water quality.